TEMUAN UANG KEPENG GAMBANGAN DESA GAMBANGAN, KECAMATAN MAESAN KABUPATEN BONDOWOSO, JAWA TIMUR: HASIL KAJIAN AWAL DAN POTENSI PEMANFAATANNYA - Sugeng Riyanto (Balai Arkeologi Yogyakarta, 2009)
This article is a result of an early study of the finding of ancient coins in Gambangan site, Bondowoso Regency, East Java. Based on the findings of the ancient coins and other artifacts, it is assumed that Gambangan site contains a small numbers of archaeological data and its distribution is limited as well. Gambangan site is supposed as a simple settlement site or non permanent settlement site closely related to Majapahit Kingdom. An early study on Gambangan site has described the potentials of the findings in academic field and in the utilization of development such as research materials, education materials and as part of tourist development.